2017
DOI: 10.3892/ijo.2017.4121
|View full text |Cite
|
Sign up to set email alerts
|

APPL1 promotes the migration of gastric cancer cells by regulating Akt2 phosphorylation

Abstract: As a multifunctional adaptor protein, APPL1 (adaptor protein containing pleckstrin homology domain, phosphotyrosine binding domain and a leucine zipper motif 1) is overexpressed in many cancers, and has been implicated in tumorigenesis and tumor progression. The present study investigated the expression of APPL1 in gastric carcinoma and the function in regulating cell migration. We investigated the expression of APPL1 in gastric carcinoma based upon The Cancer Genome Atlas (TCGA) database. The expression of AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…APPL1, or DIP13α, is a 709 amino acid endosomal protein that serves as a relay to interact with a range of proteins. 27 Notably, DM mainly results from relative insulin deficiency, which is attributed to impaired signaling or defective insulin secretion. 28 The main peripheral insulin targets, including skeletal muscles, adipose tissues, and the liver, where the APPL1 expression has been determined, indicate the involvement of APPL1 in DM.…”
Section: Discussionmentioning
confidence: 99%
“…APPL1, or DIP13α, is a 709 amino acid endosomal protein that serves as a relay to interact with a range of proteins. 27 Notably, DM mainly results from relative insulin deficiency, which is attributed to impaired signaling or defective insulin secretion. 28 The main peripheral insulin targets, including skeletal muscles, adipose tissues, and the liver, where the APPL1 expression has been determined, indicate the involvement of APPL1 in DM.…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding was different from a few studies, which found that APPL1 was highly expressed in cholangiocarcinoma (CHOL), liver hepatocellular carcinoma (LIHC), stomach adenocarcinoma (STAD), and breast cancer. Ding Oxidative Medicine and Cellular Longevity that the expression of APPL1 was upregulated in breast cancer (MCF-7) and liver cancer cells (HepG2), and they verified that APPL1 could promote the proliferation and migration of tumor cells via leptin-mediated phosphorylation of STAT3, ERK1/2, and AKT, which could explain the relevant mechanisms [31][32][33]. The clinical prognosis analysis for KIRC showed that the survival rate was significantly lower in an APPL1-downregulated condition (Figure 3).…”
Section: Discussionmentioning
confidence: 84%
“…The majority of other genes identified in the current study have also been reported to be involved in various types of cancer and diseases. These include ABCB7 in myelodysplastic syndromes (31), SFMBT1 in cervical cancer (32), and APPL1 in gastric cancer (33,34). These results may provide helpful evidence for further research into breast cancer.…”
Section: Discussionmentioning
confidence: 90%